2007
DOI: 10.1097/01.bsd.0000211240.98963.f6
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Screws in Short Segment Pedicular Fixation for Thoracic and Lumbar Fractures

Abstract: To determine the effect of adding pedicle screws at the level of a burst fracture (intermediate screws) on the stiffness of a short segment pedicle fixation, an in vitro biomechanical study was carried out. Six fresh-frozen pig lumbar spine specimens were used. The flexibility of the intact specimens was examined in flexion, extension, lateral bending, and torsion. An unstable burst fracture model was created by the dropped-mass technique. The unstable spine specimens were instrumented with pedicle screws. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 19 publications
3
65
0
1
Order By: Relevance
“…Another mid-term clinical study demonstrated superior results with the fracture-level screw combination, supporting the evidence of other reports 22. Interestingly, in most of these studies, the pedicle screws used were monoaxial, despite the current trend toward using polyaxial screws in short-segment fracture fixation 101221. On review of the literature, we found that there was a paucity of data, both clinical and biomechanical, on the use of polyaxial screw as an intermediate in unstable burst fractures, and thus this biomechanical study was instituted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another mid-term clinical study demonstrated superior results with the fracture-level screw combination, supporting the evidence of other reports 22. Interestingly, in most of these studies, the pedicle screws used were monoaxial, despite the current trend toward using polyaxial screws in short-segment fracture fixation 101221. On review of the literature, we found that there was a paucity of data, both clinical and biomechanical, on the use of polyaxial screw as an intermediate in unstable burst fractures, and thus this biomechanical study was instituted.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the pattern and nature of a spinal burst fracture in clinic is more variable and unpredictable. Anekstein et al 12. hypothesized that the true mechanical effect of the intermediate screws is less predictable in in vivo settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compared to Wiltse approach, percutaneous techniques are associated with higher doses of radiation exposure without better therapeutic outcomes [8].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of this approach are; minimal tissue trauma [6], significant reduction of intraoperative muscle retraction [7], marked reduction of operative time, protection of integrity, vascularity, nerve supply and strength of paraspinal muscles, shortening of hospitalization and minimizing development of chronic postoperative back pain [8]. There are two disadvantages of this approach.…”
Section: Introductionmentioning
confidence: 99%